The man who couldn't miss : a Stewart Hoag mystery - Handler, David, 1952- (Handler, David, 1952- Stewart Hoag mystery., 2018)
"In the next novel in David Handler's Edgar award-winning series, Stewart "Hoagy" Hoag and his beloved basset hound, Lulu, investigate a murder in a fabled Connecticut summer playhouse. Hollywood ghostwriter Stewart "Hoagy" Hoag has chronicled the rise, fall, and triumphant return of many a celebrity. At last he's enjoying his own, very welcome second act. After hitting a creative slump following the success of his debut novel, Hoagy has found inspiration again. Ensconced with his faithful but cowardly basset hound, Lulu, on a Connecticut farm belonging to his ex-wife, Oscar-winning actress Merilee Nash, he's busy working on a new novel. He's even holding out hope that he and Merilee might get together again. Life is simple and fulfilling--which of course means it's time for complications to set in"--